Effect of Unripe Berlin Banana Flour on Lipid Profile of Dyslipidemia Rats - Agustin, Firda; Febriyatna, Ayu; Damayati, Ratih Putri; Hermawan, Hendra; Faiziah, Nurul; Santoso, Razi Dwi; Wulandari, Retno Dwi (Majalah Kedokteran Bandung, 2019)
Dyslipidemia is one of the risk factors of coronary heart disease and stroke. Unripe Berlin banana flour contains chemical compounds and nutrients that may affect lipid profile. This study aimed to determine the potential effects of unripe berlin banana flour on lipid profile, especially in dyslipidemia. This experiment was conducted from July to December 2018 at the Food Analysis Laboratory of State Polytechnic of Jember and the Biomedical Laboratory of the Faculty of Dentistry, University of Jember using male wistar white rats weighed 150–200g. The rats were then divided into a negative control group consisting of normal rats (K-), a positive control group consisting of dyslipidemia rats (K+), and a treatment group consisting of dyslipidemia rats that received 0.144 g unripe berlin banana flour (UBF). Dyslipidemia condition was achieved by administering high-fat diet (HFD) for 9 weeks. Unripe banana flour was fed to the treatment group starting from the 10th weeks for 4 weeks. The measurement of pre-intervention lipid profile was performed at 9th week while the post-intervention lipid profile was measured at 13th week. Data collected were analyzed using ANOVA. Results o showed that the Berlin unripe flour (UBF) could reduce total cholesterol and LDL levels. In addition, a decrease in HDL levels in treatment group with Berlin unripe banana flour (UBF) and in the negative control group (K-). The same decrease in HDL level was also seen in the dyslipidemia group (K+). Hence, it is concluded that Berlin banana flour has the potential to improve lipid profile in dyslipidemia rats. Pengaruh Pemberian Tepung Pisang Berlin Unripe terhadap Perbaikan Profil Lipid Tikus Dislipidemia Dislipidemia merupakan faktor risiko penyakit jantung koroner dan strok. Tepung pisang berlin unripe mengandung senyawa aktif dan zat gizi yang berpengaruh terhadap profil lipid. Penelitian ini bertujuan mengetahui potensi tepung pisang berlin unripe terhadap profil lipid pada tikus jantan galur wistar model displidemia. Penelitian dilaksanakan pada bulan Juli sampai dengan Desember 2018 di Laboratorium Analisis Pangan, Politeknik Negeri Jember dan Laboratorium Biomedik, Fakultas Kedokteran Gigi, Universitas Jember. Penelitian menggunakan tikus jantan galur Wistar dengan bobot badan 150–200 gr. Kelompok perlakuan terdiri atas kelompok tikus normal (K-), tikus dislipidemia (K+), tikus dislipidemia + tepung pisang Berlin unripe dosis 0,144 gram (UBF). Perlakuan dislipidemia dilakukan dengan cara pemberian high fat diet (HFD) selama 9 minggu. Selanjutnya, pemberian UBF diberikan dalam bentuk pakan selama 4 minggu. Pengukuran profil lipid pre-intervensi (minggu ke-9) dan post-intervensi (minggu ke-13). Data dianalisis dengan uji ANOVA. Hasil penelitian menunjukkan bahwa kelompok perlakuan tepung pisang Berlin unripe (UBF) dapat menurunkan kadar kolesterol total dan LDL. Selain itu, terjadi penurunan kadar HDL pada kelompok perlakuan tepung pisang Berlin unripe (UBF) dan kelompok negatif (K-). Pada kelompok K+ juga terjadi penurunan kadar HDL. Simpulan penelitian, tepung pisang Berlin memiliki potensi terhadap perbaikan profil lipid pada tikus dislipidemia.